Decomposing systemic risk: The roles of contagion and common exposures - Grzegorz Hałaj; Ruben Hipp (European Central Bank (ECB), 2024)
We evaluate the effects of contagion and common exposure on banks' capital through a regression design inspired by the structural VAR literature and derived from the balance sheet identity. Contagion can occur through direct exposures, fire sales, and market-based sentiment, while common exposures result from portfolio overlaps. We estimate the structural regression on granular balance sheet and interbank exposure data of the Canadian banking market. First, we document that contagion varies in time, with the highest levels around the Great Financial Crisis and lowest levels during the pandemic. Second, we find that after the introduction of Basel III the relative importance of risks has changed, hinting that sources of systemic risk have changed structurally. Our new framework complements traditional stress-tests focused on single institutions by providing a holistic view of systemic risk.
Keywords: G21; C32; C51; L14; 330; Systemic Risk; Contagion; Networks; Structural estimation; Banking